Laju Percepatan Perkembangan Perbankan Syariah Melalui Penerapan Tata Kelola Syariah - Rachmad Nor Firman; Muhammad Alwi (Tasharruf : Journal of Islamic Economics and Business, 2020)
The growth and development of the Indonesian Islamic banking industry shows an increasing graph, although experiencing a slowdown. Data published by OJK shows that national Islamic banking contributed 4.81% to the market share with asset growth getting 1197% as of June 2018. At the global level, the Islamic financial services sector, including banking, controls 3% and together with Qatar, Saudi Arabia, Malaysia, the United Arab Emirates and Turkey are the driving forces of Islamic finance in the future. One of the strategic issues that becomes an obstacle is the public's misperception of Islamic banking regarding contracts, products and services that do not comply with sharia principles. Implementation of governance is an effort to accelerate the growth of Islamic banking.